THE EFFECTS OF PROBLEM-BASED LEARNING ON PROBLEM SOLVING ABILITIES AND ATTITUDES TOWARD MATHEMATICS SUBJECT OF MATHAYOMSUKSA 6 STUDENTS - Roengphot, Hathaiphat; Insombat, Bantita (Journal of Educational Review Faculty of Education in MCU, 2024)
The purposes of this research were 1) to compare the problem-solving abilities of Mathayomsuksa 6 students before and after learning by problem-based learning, 2) to compare the problem-solving abilities of Mathayomsuksa 6 students after learning by problem-based learning between students with different academic performance, 3) to study the attitude towards learning Mathematics of Mathayomsuksa 6 students after learning by problem-based learning and 4) to compare the attitude towards learning Mathematics of Mathayomsuksa 6 students after learning by problem-based learning between students with different academic performance. This research was an experimental research based on one-group pretest-posttest design. The research instruments of this research included 1) lesson plans according to problem-based learning about Basic Principles of Counting and Probability, 2) measurement of problem-solving ability about Basic Principles of Counting and Probability and 3) the attitude questionnaire about learning Mathematics. Results showed that 1) Mathayomsuksa 6 students after learning by problem-based learning had the problem-solving ability after learning higher than before learning with statistically significance at the .05 level. 2) Mathayomsuksa 6 students with different academic achievement had the different of problem-solving ability after learning by problem-based learning with statistically significance at the .05 level. 3) The attitude towards learning Mathematics the problem-based learning of Mathayomsuksa 6 students was at the good level and 4) Mathayomsuksa 6 students with different academic achievements had a different attitude toward learning Mathematics after learning by problem-based learning with statistically significance at the .05 level.